(untitled) (Law and world, 2015)
Thus, in view of the above, it can be said that the request of the tax authority must take into account not only of administrative regulations of the Administrative Procedure Code, but under the provisions of the Tax Code of the taxpayer and his tax obligations. Topics such as due to the nature of the event to ensure the payment of tax arrears – a person (the taxpayer) for the property was seized by the tax authority should not be carried out without a court decision, court Seized property of the taxpayer, the tax authority is also considering a motion to be considered by the Civil Code and the fifth row of the legal heirs of their own property, which can not be viewed as the taxpayer-owned property. At issue should be considered in relation to the Civil Code of legataris’s possession (use) of the property, which can not be dealt with by the court as the taxpayer-owned property.